Graphene reinforced polyether ether ketone nanocomposites for bone repair applications - Nan Jiang; Peijie Tan; Miaomiao He; Jie Zhang; Dan Sun; Songsong Zhu (Polymer Testing, 2021)
To improve the performance of polyether ether ketone matrix (PEEK) in hard tissue repair and replacement applications, we fabricated graphene nanoplatelet (G) reinforced PEEK with different filler weight concentrations (0.1%–5%) through injection moulding. The mechanical properties, surface morphology, chemical composition and thermal stability of the composites have been characterized. The biocompatibility has been assessed in vitro and the bone repair function of the composite implants have been assessed in vivo using a rabbit mandibular bone defect model. Mechanical testing results suggest that the composite samples have compressive moduli similar to that of the natural bone. Although addition of G into PEEK does not significantly influence the composite tensile, flexural or compressive moduli, it can significantly enhance the ductility and toughness of the material. On the other hand, all G-reinforced PEEK implants demonstrated enhanced adhesion and diﬀerentiation of rat bone marrow stromal cells (BMSCs), with 5% G-PEEK showing the highest bioactivity among all samples. The in vivo osseointegration data further revealed that 5% G-PEEK has the best effect in promoting osseointegration and bone regeneration, in both early stage and late stage bone re-growth. Study shows that our G-reinforced PEEK-based implants provides a promising strategy for enhancing the performance of future regenerative bone implants.